All about the money? A cross-national study of parties' relations with trade unions in 12 western democracies. (May 2021) - Allern, Elin Haugsgjerd; Hansen, Vibeke Wøien; Otjes, Simon; Rasmussen, Anne; Røed, Maiken; Bale, Tim
This article examines political parties' approach to trade unions and the role of private and public party finance in contemporary democracies. We suggest that both unions' direct donations and states' party finance regimes may account for variation in the strength of parties' organizational links to unions. We investigate this argument with a new data set covering parties historically aligned with trade unions and union confederations in 12 mature democracies. Our empirical analysis provides support for the hypothesis that financial contributions are positively associated with stronger organizational links but also suggests that this relationship is constrained by the level of public subsidies and state regulation of donations. The findings point to the need for more research on how private and public money affects parties' interactions with civil society actors.